Rational Design of Metal Oxide-Based Cathodes for Efficient Dye-Sensitized Solar Cells - Wang, Wei; Xu, X.; Liu, Yu; Zhong, Y.; Shao, Zongping (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim., 2018)
Recently, there is an urgent need for alternative energy resources due to the nonrenewable nature of fossil fuels and increasing CO2greenhouse gas emissions. The photovoltaic technologies which directly utilize the abundant and sustainable solar energy are critical. Among various photovoltaic devices (solar cells), dye-sensitized solar cells (DSSCs) have gained increasing attention due to their high efficiency and easy fabrication process in the past decade. The cathode is a critical part in DSSCs while the benchmark Pt cathode suffers from high cost and scarcity. Thus, the development of alternative Pt-free cathodes has attracted significant attention with the aim to heighten the cost competitiveness of DSSCs. Among various cathodes, metal oxides are of growing interest due to their superior activity, robust stability, and low cost. Simple oxides such as WO3and SnO2are used as cathodes for DSSCs. Considering the fixed atomic environment in simple oxides, complex oxides are more attractive as cathodes because of their more flexible physical and chemical properties. This review attempts to present the rational design of simple/complex metal oxide-based cathodes in DSSCs and then to provide useful guidance for the future design of Pt-free cathodes. The demonstrated design strategies can be extended to other electrocatalysis-based applications.